Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/vde.13105
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin treatment of canine multidrug‐resistant meticillin‐resistant staphylococcal pyoderma: A retrospective study of 51 cases

Abstract: Background: Rifampicin (RFP) is a potential treatment for canine multidrugresistant (MDR) meticillin-resistant staphylococci (MRS), yet the use of lower doses based on recent MIC data has not been evaluated in vivo.Hypothesis/Objectives: To provide information on the efficacy and safety of low-dose range RFP (≤6 mg/kg/day) for the treatment of canine MDR MRS pyoderma.Animals: Fifty-one client-owned dogs. Materials and methods:Retrospective review of dogs medical records. Dogs were from 11 US dermatology referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Bacterial culture and sensitivity testing is frequently ignored in CDP and CIF diagnostic workup for which empiric therapy is still erroneously considered suitable in certain cases, particularly during first-time or untreated infections [ 5 ] Some authors have demonstrated that selected antimicrobials widely considered to be effective during deep bacterial skin infection (i.e., β-Lactam, macrolides, lincosamides, and potentiated sulfonamides) may promote establishment of methicillin-resistant strains [ 7 , 31 ]. On the other hand, other authors highlighted a possible efficacy of rifampicin for the treatment of multidrug resistant staphylococcal infections, requiring concurrent topical antimicrobial administration to obtain a complete resolution in near 80% of dogs, despite more studies to assess the safety profile are needed [ 32 ]. Many MDR staphylococcal isolates of the present study resulted to be resistant to fluoroquinolones as previously demonstrated by other authors during MDR infections [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial culture and sensitivity testing is frequently ignored in CDP and CIF diagnostic workup for which empiric therapy is still erroneously considered suitable in certain cases, particularly during first-time or untreated infections [ 5 ] Some authors have demonstrated that selected antimicrobials widely considered to be effective during deep bacterial skin infection (i.e., β-Lactam, macrolides, lincosamides, and potentiated sulfonamides) may promote establishment of methicillin-resistant strains [ 7 , 31 ]. On the other hand, other authors highlighted a possible efficacy of rifampicin for the treatment of multidrug resistant staphylococcal infections, requiring concurrent topical antimicrobial administration to obtain a complete resolution in near 80% of dogs, despite more studies to assess the safety profile are needed [ 32 ]. Many MDR staphylococcal isolates of the present study resulted to be resistant to fluoroquinolones as previously demonstrated by other authors during MDR infections [ 7 ].…”
Section: Discussionmentioning
confidence: 99%